The performative in educational research: an essay on species that live on the edges of the road (Praxis Educativa, 2025)
This work is part of the narrative thread of a teaching, research, and outreach project entitled "Rivers and Seas, Like Each Other," developed jointly by faculty and students from the National Universities of Litoral and Mar del Plata since 2022. It presents a reading practice and dialogic inquiry into the political nature of performativity, poetics as a strategy for recovering childhood memories, experientiality as a feature of educational research, and the relationship between narrative and futurity as a horizon of possibility. Polyphonic writing integrates contributions from diverse disciplinary fields, such as literature, philosophy, education, and botany, among others. As the third link in a trilogy, it recapitulates partial conclusions and includes a collective writing practice on the act of narrating ourselves.
Keywords: narrative research, education, performance, autobiography, childhood memories